Eco-development of oil and gas industry: CCUS-EOR technology - Yan, Liangzhu; Hu, Jiajia; Fang, Qiongyao; Xia, Xueqing; Lei, Banyu; Deng, Qiao (Frontiers in Earth Science, 2023)
The current status and development prospects of CCUS-EOR technology development are sorted out from the perspective of ecological development. A good foundation is laid to promote the world low-carbon development pattern and the development of CCUS-EOR technology in oil-rich, low-permeability reservoirs. By analyzing the differences between China and the United States regarding the technology level, application scale, and production effect, the development gaps between different countries in terms of CO2 burial for enhanced oil and gas recovery are derived. In response to these gaps, recommendations for responsive technology research and supporting infrastructure construction are proposed, which are of reference significance for advancing the development of large-scale CCUS technology for all of humanity.